Effect of Salt on the Quality of Stone Milled Whole Wheat Flour and Dried Noodles - Mengdi CAI; Chunxia SHEN; Yuhui LI; Shuangli XIONG; Feng LI (Shipin gongye ke-ji, 2023)
In order to improve the quality of dried noodles, the effect of different salt additions on the pasting and farinograph properties of stone milled whole wheat flour, dough color, cooking, sensory, texture properties and antioxidant activity of noodles was explored. The results showed that the peak viscosity and breakdown of whole wheat flour increased first and then decreased, the water absorption and degree of softening decreased continuously, and the pasting temperature, dough development and stability time increased constantly with the increase of salt. After the addition of salt, the brightness of whole wheat dough in the 0 h group increased significantly (P<0.05), but its red-green value and yellow-blue value decreased significantly (P<0.05). When the amount of salt added was 2%, the cooking loss rate of noodles and turbidity of noodle soup reached the maximum, which were 7.93% and 0.162, respectively. The ABTS+• scavenging ability and total reduction ability of cooked noodles reached the maximum, which were 33.53% and 0.455, respectively. Within the range of 0%~2%, the hardness, gumminess, and chewiness of noodles decreased with the increase of salt. In summary, the overall quality of whole wheat dough and noodles was the best when the amount of salt added was 1%.